The Role of Primary School Teachers in Inclusive Education for Character Development - Afiz Aditia Pratama; Diah Ayu Stianingrum; Neza Virgianti (EDOVA JOURNAL : Education for Nation Development Journal, 2026)
The increasing diversity of student characteristics in primary schools, including the presence of students with special educational needs in regular classrooms, necessitates the implementation of inclusive education that focuses not only on academic achievement but also on students’ character development. In this context, teachers play a strategic role as facilitators, mediators, and mentors in creating learning environments that value diversity and inclusivity. This study aims to analyze the role of primary school teachers in fostering students’ character development through inclusive education. The study employed a library research method by examining various scholarly articles, books, and relevant documents related to inclusive education and character education. Data were collected through document analysis, while the data were analyzed using content analysis techniques. The findings indicate that character development within inclusive learning environments is promoted through the implementation of adaptive instructional strategies, authentic assessment practices, positive behavior habituation, and collaboration among teachers, parents, and other educational professionals. The most prominent character values developed include empathy, tolerance, responsibility, cooperation, and respect for diversity. Furthermore, the findings reveal that the consistent integration of character values into inclusive educational practices contributes to strengthening students’ social-emotional development, enhancing positive peer interactions, and fostering a more inclusive and humane school culture.